Unlocking MSME Performance: The Interplay of Financial Literacy, Financial Inclusion, and Financial Technology Lending with Venture Capital Mediation - Hasanudin Hasanudin; Fahrudin Panigfat (Shirkah: Journal of Economics and Business, 2024)
Studying the dynamic relationship among financial literacy, financial inclusion, fintech lending, and business capital mediation in the context of MSME performance is intriguing due to the intricate interconnections between these variables. This paper sought to assess the effect of financial literacy, financial inclusion, and fintech lending on the MSME performance in North Maluku Province, Sula Islands Regency, Sanana District, Indonesia. This research employed business capital as the mediating variable. Using a structural equation modelling, this study indicates that financial literacy, financial inclusion, and fintech lending have a positive and significant effect on the performance of micro, small, and medium enterprises. The presence of business capital can serve as a mediating factor in how financial literacy, financial inclusion, and fintech lending affect the performance of micro, small, and medium enterprises.